Resilient Romans: Cross-Sectional Evidence for Long-Term Functional Consequences of Extremity Trauma - Gilmour, Rebecca Jeanne (My University, 2017)
Long-term repercussions of extremity trauma can include fracture mal- and non-union, osteoarthritis, pain, and impairment of physical movement, which can result in disuse of the limb and eventual bone loss. Although trauma is commonly investigated in palaeopathology, the functional repercussions of injuries are not typically considered. By integrating palaeopathological fracture analyses and biomechanical investigations of cross-sectional properties, this thesis explores individual and group experiences of extremity fracture risks, responses, and consequences at two Roman sites. Adults from 1st-4th century AD Roman cemeteries at Ancaster, UK (n=181), and Vagnari, Italy (n=66), were examined for limb fractures. Data on fracture type, location, malunion, and associated infection and osteoarthritis were collected. Bone areas and asymmetries were calculated using biplanar radiographs for individuals without fractures, and compared to those of individuals with fractures. Patterns in bone amounts and asymmetries associated with fracture attributes were identified. Extremity fractures were observed in 39 individuals from Ancaster and 12 individuals from Vagnari, but the prevalence rates did not differ between the sites. Cross-sectional properties suggested that compared to Ancaster, individuals living at Vagnari experienced greater mechanical loading (i.e., larger bone areas). Disuse of a fractured limb was only identified in two old adult individuals from Ancaster; no Vagnari individuals had evidence for post-traumatic dysfunction. Functional consequences of injuries were not associated with observable fracture attributes (e.g., fracture type, malunion), meaning that physical impairment cannot be recognized based only on an injury’s appearance. By incorporating biomechanical methods in palaeopathological analyses of trauma, this thesis reveals the physical experiences of injury acquisition and recovery among residents of Ancaster and Vagnari over the life course. The relative absence of post-traumatic disuse speaks to the resilience of Romans at these sites, and contributes to the growing literature on the human experience of trauma and impairment in the past.
Long-Term Consequences of Roman Extremity Fractures
Keywords: Palaeopathology; Biomechanics; Trauma Analyses; Extremity Fractures; Impairment; Roman Period; Post-Traumatic Dysfunction